PENGARUH KEBIJAKAN LOW COST GREEN CAR TERHADAP STRATEGI NISSAN MOTOR CORPORATION MENGUASAI PASAR OTOMOTIF DI INDONESIA - Purba, Samuel Berliando Hasiholan; Nizmi, Yusnarida Eka (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research discusses the influence of Low Cost Green Car policy to strategy Nissan Motors Corporation dominate the automotive market in Indonesia. In 2013 Indonesia by Minister of Industry issued Low Cost Green Car policy. To face the enthusiasts of Low Cost Green Car that much, Nissan issued old products are very popular in Indonesia called Datsun.Perspective that used in this research is Neoliberalism perspective. The theory used in this research is the competitive theory by Michael Porter's. According to this theory, competitive advantage is the advantage by delivering greater value to customers, the price is cheaper and give more advantages from its competitors.The influence of Low Cost Green Car policy to the strategy of Nissan Motor Corporation in dominate the automotive market in Indonesia is Nissan follow low cost green car policy with its subsidiary company registered Datsun successfully. This is proven from the beginning of the presence of the first model of Datsun like Datsun Go+ Panca which began in May. Datsun sales continue to increase each month until November. The success of the Nissan strategy was proven with the launch of a second product that LCGC manifold Datsun Go Panca Hatchback.Keywords: Low Cost Green Car, Nissan Motor Corporation, Datsun Motor Corporation